Effect of particle size on selective hydrogenation of cinnamaldehyde by Pt encapsulated in mesoporous silica - Prashar, Atul K.; Mayadevi, S.; Devi, R. Nandini (Catalysis Communications, 2012)
Pt nanoparticles of various sizes, viz. 8. 4.9, 3.6 and 1.8 nm were encapsulated in 2D hexagonal mesoporous silica by in-situ synthesis as well as post synthetic modifications so that the final catalyst composition was <= 1 wt.% Pt/SiO2. A kinetic analysis of the effect of particle size on selective hydrogenation of cinnamaldehyde was carried out on these catalysts. It was found that the materials, even at such low loading of Pt, were very active for the hydrogenation and selective for the desired product, cinnamyl alcohol. Among the different particle sizes, selectivity was found to be the highest on 8 nm particles. Kinetic analysis shows that the reaction follows a consecutive reaction pathway. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehydes; Cinnamaldehyde hydrogenation; Kinetic analysis; Mesoporous silica; Pt nanoparticles; Selective hydrogenation